Crime and the Global Political Economy - Edited by H. Richard Friman (New Delhi Viva Books, 2010)
Crime has gone global. Conventional explanations point to ways in which criminals have exploited technological innovations, deregulation, and free markets to triumph over state sovereignty. "Crime and the Global Political Economy" reveals a more complex reality. Taking as a point of departure the reality that state and societal actors are challenged by - and complicit in - the expansion of criminal activities on a global scale, the authors demonstrate that the political, economic, and normative agendas of those actors lead to selective criminalization and diverse patterns of compliance with prohibition regimes.
Include Bibliograpy
Keywords: Crime and Globalization -- Transnational Crime -- Transnational Crime